Analysis of the domestic market of compressor and ultrasonic nebulizers - Brytanova, Т. S.; Samko, A. V.; Британова, Тетяна Сергіївна; Самко, Анатолій Васильович (Запорізький державний медичний університет, 2022)
The aim of the work is to organize informational files about compressors and ultrasonic nebulizers determination of actuality and availability in marketing analysis of the domestic market. Materials and methods. Data from the Apteka.UA and the official website of Tabletki.ua were used to analyze the brand and assortment structure of ultrasonic and compressor nebulizers. The search analytical, systematic, comparative, and statistical methods and methods of mathematical and logical analysis were used in the work. Results. The analysis of the market of assortment and brand structures of the compressor and ultrasonic nebulizers was carried out. The obtained results showed the presence on the market of 16 manufacturers from 10 countries in the world of compressor nebulizers and 9 manufacturers from 7 countries in the world of ultrasonic nebulizers. Among them, the largest suppliers were identified, such as Omron Healthcare (Japan) and LLC Medhouse Swiss GmbH (Ukraine). The calculated stress coefficient indicated greater competition between compressor manufacturers (Kvi = 0.94) compared to ultrasonic (Kvi = 0.88) nebulizers. The level of monopolization was determined using the Herfindahl–Hirschman index. The results indicated a moderately concentrated market for both types of nebulizers. Analysis of socio-economic affordability by indicators of price liquidity ratio and solvency adequacy noted low availability of this group of goods for consumers of pharmacies. Мета роботи – формування інформаційного масиву про компресорні й ультразвукові небулайзери, визначення актуальності їхньої доступності на підставі маркетингового аналізу вітчизняного ринку. Матеріали та методи. Для здійснення аналізу фірмової та асортиментної структури компресорних та ультразвукових небулайзерів використали дані «Щотижневика АПТЕКА» та офіційного сайту Tabletki.ua. Застосували системно-аналітичний, математико-статистичний і порівняльний методи аналізу. Результати. Здійснили аналіз ринку асортиментної та фірмової структур компресорних та ультразвукових небулайзерів. У результаті встановили наявність на ринку 16 фірм-виробників компресорних небулайзерів із 10 країн світу, а також 9 фірм-виробників ультразвукових небулайзерів із 7 країн світу. Визначили найбільших постачальників: Omron Healthcare (Японія) і ТОВ «Медхаус Свіс ГМБХ» (Україна).
Аналіз вітчизняного ринку компресорних та ультразвукових небулайзерів
Brytanova T. S. - ORCID ID: 0000-0003-1805-4552; Samko A. V. - ORCID ID: 0000-0002-3182-5588.
Keywords: pharmaceutical preparations; marketing; ultrasonic nebulizers; compressor nebulizers; analysis; pricing; фармацевтичний ринок; ультразвукові небулайзери; компресорні небулайзери; аналіз; цінова кон’юнктура